Dentifrício fluoretado suplementado com hexametafosfato de sódio sobre o processo de desmineralização do esmalte: estudos in vitro e in situ - Camara, Danielle Mendes da [UNESP] (2015)
The objective of this study was to evaluate the ability of conventional dentifrices (1100 ppm F) supplemented with sodium hexametaphosphate (HMP), in reducing enamel demineralization in vitro and in situ. In the study of demineralization of bovine enamel blocks (n = 60) selected by the initial surface hardness (SHI) were divided into five groups of dentifrices (n = 12) without fluoride and HMP without (Placebo); conventional dentifrice 1100 ppm F (1100F); 1100 ppm F associated 0.5% of HMP (1100FHMP0.5%), 1100 ppm F associated 1% of HMP (1100FHMP1%) and 1100 ppm F associated 2% of HMP (1100FHMP2%). The blocks were subjected to pH cycling for five days, and then treatment performed with the respective dentifrices 2x / day. Next, we determined final surface hardness (SHf), surface hardness loss (% SH), integrated differential hardness (ΔIH) and integrated loss of subsurface hardness (ΔKHN) and fluoride (F) in the enamel. The results were submitted to one-way ANOVA followed by the Student-Newman-Keuls test (p <0.001). The group 1100FHMP1% had the lowest mineral loss (SH%, ΔKHN and ΔIH) followed in 1100FHMP0.5% (p <0.001). 1100FHMP1% group had the same concentration of 1100 ppm F in group F. For the study of enamel in situ bovine enamel blocks (n = 144) were selected for the surface hardness and divided into three groups: Placebo (placebo), 1100 ppm F (1100F), 1100 ppm F associated 1% of HMP (1100FHMP1%). Twelve volunteers wore palatal appliances with four enamel blocks for seven days, and brushing performed 3x / day with the palatal device within the oral cavity and the cariogenic challenge with sucrose 30% at pre-established times. After 7 days, SH% was determined, ΔKHN and fluoride (F), calcium (Ca) and phosphorus (P) in enamel. The biofilms formed were analyzed for the concentration of F, Ca, P and extracellular polysaccharide (EPS)...